Efektivitas Kerangka Hukum Perlindungan Konsumen terhadap Fintech Syariah di Indonesia: Studi Yuridis Normatif atas Peran OJK dan Mekanisme Penyelesaian Sengketa - Njatrijani, Rinitami; Oktaviana, Ria Rindika (Faculty of Law, Diponegoro University, 2026)
This research is motivated by the rapid development of Islamic fintech in Indonesia, which presents new legal risks, while the existing consumer protection legal framework has not fully addressed the complexity of digital transactions. This study addresses the effectiveness of the consumer protection legal framework for Islamic fintech following the enactment of Law Number 4 of 2023, the role of the Financial Services Authority (OJK), and the applicable dispute resolution mechanisms. It aims to analyze the effectiveness of these regulations, critically examine the role of the OJK, and evaluate the dispute resolution mechanism through LAPS-SJK. The findings offer theoretical benefits for the development of consumer protection law and practical benefits for stakeholders in strengthening the Islamic fintech ecosystem. This research employs a normative juridical method with statutory and conceptual approaches, utilizing secondary data in the form of literature and relevant court decisions. The results indicate that OJK regulations have adopted consumer protection principles and sharia values; however, their implementation continues to face challenges, such as low digital financial literacy, weak provider compliance, and limited consumer access to non-litigation dispute resolution mechanisms. This study recommends strengthening technology-based supervision, harmonizing regulations, and expanding consumer education.